tert-Butyl Hypochlorite Induced Cyclization of Ethyl 2-(N-Arylcarbamoyl)-2-iminoacetates - Li, Dianjun; Li, Ying; Yu, Wei (Synthesis, 2017)
Ethyl 2-(N-arylcarbamoyl)-2-iminoacetates can be transformed into the corresponding quinoxalin-2-ones in high yield by using the oxidation system of tert-butyl hypochlorite, tetrabutylammonium iodide and tetrabutylammonium chloride. Oxygen exhibits a beneficial effect on the reaction. The reaction is proposed to follow an iminyl radical cyclization mechanism where azaspirocyclohexadienylperoxyl radical is formed as a key intermediate. The quinoxalin-2-one is derived from the azaspirocyclohexadienylperoxyl radical via concurrent oxygen extrusion and rearrangement.
Keywords: cyclization; radical reaction; iminyl radical; quinoxalin-2-ones; oxygen; peroxyl radical